2018
DOI: 10.1016/j.theriogenology.2018.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Different protocols using PGF2α as ovulation inducer in Nelore cows subjected to estradiol-progesterone timed AI based protocols

Abstract: The objective of this study was to evaluate the effect of a PGFα-analogue (PGF) on ovulation and pregnancy rates after timed artificial insemination (TAI) in cattle. In Experiment 1 cows received an intravaginal progesterone-releasing device (CIDR) plus 2 mg im of estradiol benzoate (EB) on Day 0. The CIDR devices were removed on Day 8, and all cows received 150 μg im of d-cloprostenol (PGFα-analogue), 300 IU of eCG and 1 mg of estradiol cypionate (ECP) im. On Day 9, cows were randomly assigned into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
(24 reference statements)
0
9
1
2
Order By: Relevance
“…In addition, strategies established to manipulate follicular wave dynamics can optimize the efficiency of embryo production techniques. The diameter size of ovulating follicle in this present study is smaller than in crossbred cows was 13.6 ±0.5 mm in ECP protocol and 13.5± 0.7 mm [15], was 13 mm [2]. However this study is similar to [16] that diameter size of ovulating follicle range from ≤6mm to ≥ 9 mm with mean is 13.1±0.26 mm in the GnRH-FSH analogue, 8.2 ±1.16 mm in the hMG, and 4.2±1.07 mm in the eCG-FSH.…”
Section: A Ovarian Responses Of Cows Treated Using Gnrh Plus Progestcontrasting
confidence: 63%
“…In addition, strategies established to manipulate follicular wave dynamics can optimize the efficiency of embryo production techniques. The diameter size of ovulating follicle in this present study is smaller than in crossbred cows was 13.6 ±0.5 mm in ECP protocol and 13.5± 0.7 mm [15], was 13 mm [2]. However this study is similar to [16] that diameter size of ovulating follicle range from ≤6mm to ≥ 9 mm with mean is 13.1±0.26 mm in the GnRH-FSH analogue, 8.2 ±1.16 mm in the hMG, and 4.2±1.07 mm in the eCG-FSH.…”
Section: A Ovarian Responses Of Cows Treated Using Gnrh Plus Progestcontrasting
confidence: 63%
“…Although the number of animals included in the present study is low, these evidences lead us to infer that PGF has no ovulatory effect in buffaloes. Previous studies have indicated that d-cloprostenol has an ovulatory effect similar to that of EB in TAI protocols, resulting in similar ovulation and pregnancy rates in dairy (Pfeifer et al, 2016;Castro et al, 2018) and beef cows (Pfeifer et al, 2014(Pfeifer et al, , 2018. Moreover, the injection of PGF has also been reported to act as an ovulatory stimulus in prepubertal heifers (Pfeifer et al, 2009;Leonardi et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, understanding the role of PGF in ovulation is essential for the development of more efficient techniques and methods for the control of reproductive cycles in cows. In this sense, it is known that administration of commercial analogs of PGF results in ovulation in sheep (Davies et al, 2006) and cattle exposed to different ovulation synchronization protocols (Pfeifer et al, 2014;Pfeifer et al, 2016;Pfeifer et al, 2018;Castro et al, 2017). Additionally, the effect of PGF on ovulation is independent of its luteolytic action, since it is also able to induce ovulation in prepubertal heifers (Leonardi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, PGF is also able to hasten and synchronize ovulation in cattle (Pfeifer et al, 2014;Pfeifer et al, 2016;Castro et al, 2017) independent of its luteolytic action (Leonardi et al, 2012). Previously, we observed that d-Cloprostenol (PGF analog) had a similar ovulatory effect to that of estradiol benzoate in timed artificial insemination (TAI) protocols, resulting in similar ovulation and pregnancy rates in dairy (Pfeifer et al, 2016;Castro et al, 2017) and beef cows (Pfeifer et al, 2014;Pfeifer et al, 2018). Despite this, the mechanism of action for injectable PGF to induce ovulation in cattle is still unknown.…”
Section: Introductionmentioning
confidence: 99%